Perubahan Ekonomi dan Perkembangan Islam di Bengkulu Akhir Abad XIX Sampai Awal Abad XX: The Change of Economic and Islamic Development at Bengkulu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The Islamic process at Bengkulu could not be separated with the economic activities, especially with the pepper merchandise. The peppe's market at Bengkulu had increased since the XVI's century had attracted, some merchants from Banten, Aceh, and Minangkabau. The Islamic propagation at 13engkulu would be more intensive when Banten and Aceh kingdoms reached their authority to claim the pepper merchant route. The coming of Islamic religion at Bengkulu, could change the Animism and Dynamism faiths and also from Hinduism-Buddhism to be moslem faith, beside that was also as a one factor in making a new tradition for the peoples of Bengkulu. Until the early of )0( centuries, the Islamic process at Bengkulu still continue, especially at the rural areas which they were still on Animism faith since most of them were traditional peasants. The Islamic propagation were at the area as Manna, Seluma, Pasemah Hulu Manna and also Kaur propagated by religion theachers (most of them were ever pilgrim at Mecca as Hajj). In conformity with the Islamic growth, the economic living for Bengkulu peoples growing vastly for the XIX centuries. On that time, with the growing of commercialization, the Bengktilu peoples were especially foe the peasants, the Bengkulu community moslem faith, they faced the commercialization trend with rational thought. With the new era in economic growth responded with opening new production land for agricultural commodities specially coffee plants. Lastly these area had become a rich land since planted with export commodities. The vast economic growth would open social mobility for the peoples, especially for moslem community and made more opportunity to the peoples going to. Mecca since 1913. The prospherity reflected also from the way of peoples in making luxury houses and cloths. Beside that shown from their married culture in the form "perkawinan jujur" (honesty marriage) which need much money to do that.